Pengaruh Pembelajaran Diklat Teknis Substantif Peningkatan Kompetensi PKG/PKB Terhadap Efikasi Diri dan Motivasi Berprestasi Guru Madrasah - Asih Aryani (Jurnal Kewidyaiswaraan, 2019)
The purpose of this study was to find out the significant direct effect of Substantive Technical Training Learning Competency Improvement PKG and PKB which was followed to Self Efficacy, knowing the significant direct effect of Substantive Technical Training Learning PKG and PKB Competency Improvement which was followed to achievement motivation, and knowing the direct influence Significant Substantive Technical Training Learning Competency Improvement PKG and PKB were followed for achievement motivation through self-efficacy. The population of the study was the alumni of the Substantive Technical Training of PKG and PKB Competence Improvement, with a total sample of 60 people. Data was collected through questionnaires distributed and analyzed by SPSS. The results showed that a) there was a significant direct effect of Substantive Technical Training Learning Competency Improvement of PKG and PKB which was followed for Self Efficacy. b) There is a significant direct effect of Substantive Technical Training Learning PKG and PKB Competence Improvement which is followed to Achievement Motivation. c) There is a significant direct effect of Substantive Technical Training Learning Competency Improvement on PKG and PKB followed by Achievement Motivation through Self Efficacy.